Citizen nothoi? The cases of Phile (Isaeus 3) and the two ‘Mantitheuses’ (Dem. 39 and [Dem.] 40) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2025)
This article defends arguments expressed in an earlier article published in Polis 36 (2019), against the recent critique of Brenda Griffith-Williams (2020 and 2023), about the role of nothoi in the democratic polis. The evidence of Dem. 39 (Against Boeothus I), [Dem.] 40 (Against Boeothus II) and Isaeus 3 (On the Estate of Pyrrhus) shows that nothoi could be citizens at Athens, despite the assertions of many modern scholars to the contrary, and that the chief limitation which nothoi faced was to do with inheritance entitlements. A careful examination of the case against Boeothus shows that the issue at stake was the inheritance of Mantitheus’ estate, not citizenship, even though the latter is at several points dragged in for rhetorical reasons. Similarly, Isaeus’ third speech on closer analysis gives an overwhelmingly probable indication, though disputed by many scholars, that the daughter of Pyrrhus, a woman alternatively called Phile and Cleitarete, who married an Athenian named Xenocles, was an illegitimate daughter (nothe) of the deceased Pyrrhus, the rights to whose estate were up for dispute. These speeches give further confirmation to my earlier argument that legitimacy at Athens carried two distinct senses: citizenship legitimacy, which from 451/0 meant having two Athenian parents to whom the inductee to a deme could point on his eighteenth birthday, and engyetic legitimacy, which is what was required for inductees, male and female, to phratries.
Keywords: Citizenship; nothoi; legitimacy; inheritance; demes; phratries